Enhanced piezoelectric properties in M (M = Co or Zn)-doped Ba0.99Ca0.01 Ti0.98Zr0.02O3 ceramics. Issue 11 (1st August 2020) - Sun, Mingze; Du, Juan; Chen, Chong; Fu, Peng; Li, Peng; Hao, Jigong; Yue, Zhenxing; Li, Wei
Abstract: In this study, (Ba0.99 Ca0.01 )(Ti0.98 Zr0.02 )O3 - x mol% M (M = Co or Zn) (0 ≤ x ≤ 1.0) (BCZT- x M) piezoelectric ceramics with enhanced piezoelectric properties were prepared by a conventional solid-state synthesis method. The effects of different doping amounts of M on the phase structure, microstructure, dielectric properties, and piezoelectric properties of the BCZT- x M ceramics were studied systematically. Results showed that Co doping markedly decreased the average grain size, whereas Zn doping slightly decreased the grain size. The piezoelectric coefficient of the BCZT- x M ceramics increased by 30% after appropriate M doping. The mechanisms of enhancing the piezoelectric properties of the BCZT ceramics by Co and Zn doping differed. For the BCZT- x Co ceramics, Co doping induced drastic lattice distortion and enhanced the crystal disorder distribution, thereby enhancing the piezoelectric properties. For the BCZT- x Zn ceramics, the enhancement of piezoelectric properties could be attributed to the large grain size and dense microstructure. The optimum ferroelectric properties ( P r = 15.9 μC/cm 2, E c = 5.7 kV/cm) were obtained in the BCZT-0.2Co ceramics. This study provides a novel paradigm for designing high piezoelectric materials.